Racial Differences in Survival From Epithelial Ovarian Cancer Are Associated With Stage at Diagnosis and Use of Neoadjuvant Therapy: A 10-Year Single-Institution Experience With a Racially Diverse Urban Population. Issue 4 (1st May 2018) - Miller, Eirwen M.; Tymon-Rosario, Joan; Strickler, Howard D.; Xie, Xianhong; Xue, Xiaonan; Kuo, Dennis Y.S.; Makhija, Sharmila K.; Nevadunsky, Nicole S.
Abstract : Objective: The aim of this study was to evaluate the racial/ethnic disparities in ovarian cancer survival in a diverse population. Methods: We performed a retrospective cohort study evaluating all patients with epithelial ovarian cancer who received primary treatment at Montefiore Medical Center from 2005 to 2015. Clinicopathologic and survival data were abstracted from medical records. Two-sided statistical analyses were performed using SAS 9.3. Results: Three hundred forty-four evaluable patients were identified: 85 (25%) black, 107 (31%) white, 74 (21%) Hispanic, and 78 (23%) other. Black patients were more likely to present with stage IV disease ( P = 0.01) and receive neoadjuvant chemotherapy ( P < 0.01). By Kaplan-Meier survival analysis, black race was associated with worse recurrence-free survival ( P = 0.01) when compared with white race. In multivariate Cox regression model including treatment and stage, race was no longer associated with survival. In a separate multivariate analysis, utilization of neoadjuvant chemotherapy was associated with black race (odds ratio 4.03; 95% confidence interval, 1.56–10.38; P < 0.01) and stage IV disease (odds ratio 3.44; 95% confidence interval, 1.66–7.12; P < 0.01). Conclusions: In a racially/ethnically diverse population with ovarian cancer, black women had poorer disease-free survival than whites, although this was statistically accounted for by stage at diagnosis and use of neoadjuvant therapy. Research is needed to determine how differences in access/utilization of care and genetic differences in tumor biology may impact late stage diagnosis and use of neoadjuvant chemotherapy among black ovarian cancer patients.